Analyzing The Influence of Strategic Agility, Innovation Capability and Organizational Readiness on The Performance of PT Pegadaian - Manurung, Maria Indah Sri R; Sudhartio, Lily (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2024)
With global economic growth and environmental changes occurring, there are challenges and opportunities for business growth. Increasing competitiveness is a requirement to maximize opportunities and be better prepared for business competition. The right strategy will make the company superior. In most cases, superior business strategies based on superior resources and capabilities are considered obsolete and irrelevant in the face of environmental changes. Companies must increase their competitiveness by building business models through Strategic Agility and Innovation Capability as well as Organizational Readiness. Data was collected from 240 Branch Heads of PT. Pegadaian throughout Indonesia. Data collection was carried out through questionnaires. Data analysis was carried out through structural equation modeling using Smart-PLS. A deeper understanding of the interactions and dynamics between the Strategic Agility, Innovation Capability and Organizational Readiness variables on PT Performance. The pawnshop, as well as policy implications, emphasize crucial aspects that organizations need to pay attention to in improving their performance. This research can be the basis for developing a more comprehensive theory about how Strategic Agility, Innovation Capability and Organizational Readiness are interrelated and influence PT Performance. Pawnshop. This can enrich our understanding of the internal dynamics of organizations in the face of innovation and change. This research can provide valuable guidance for organizational leaders in making strategic decisions regarding innovation development, change management, and performance improvement. As well as implementing changes necessary to improve organizational readiness and performance, this can help in directing organizational resources and strategies more effectively.